Is Leadership Antidisciplinary? A Krebs Cycle of Creativity Approach With Game-Based Applications - Patel, Sanket; Lasley , Joseph (Journal of Leadership, Accountability and Ethics, 2021)
Leadership has been conceptualized as a complex interaction between contexts, leaders, and followers in an interdisciplinary paradigm. This paper explores a reorientation from an interdisciplinary to an antidisciplinary paradigm of leadership to help make meaning of the broad, often incongruent theories. This is proposed through the use of the Krebs Cycle of Creativity (KCC) as a novel philosophical heuristic. In practice, KCC may be used to conceptually facilitate constructive brainstorming around topics of innovation or problem solving across the disciplinary silos similar to how we used it to understand game-based leadership applications.